2001
DOI: 10.1359/jbmr.2001.16.12.2232
|View full text |Cite
|
Sign up to set email alerts
|

Arthrodesis of Lumbar Spine Transverse Processes Using Nacre in Rabbit

Abstract: This study compares the osteogenic effects of nacre and autogenous bone grafts in a rabbit model of lumbar spine transverse process arthrodesis. A total of 15 rabbits were processed for arthrodesis between the fifth and sixth lumbar vertebrae using nacre powder mixed with autologous blood or autogenous iliac crest bone. Control rabbits were sham operated. Sample vertebrae were removed from the nacre-implanted rabbits at 2, 5, and 11 weeks postsurgery. The autogenous bone graft and sham-operated groups were pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 30 publications
(60 reference statements)
1
20
0
Order By: Relevance
“…Recent studies revealed that nacre contains one or more signal molecules capable of activating osteogenic bone cells, in vivo and in vitro, leading to bone formation [19,20]. Water-soluble molecules diffusing from nacre powder are recognized by mammalian cells and induce recruitment and differentiation of fibroblasts from the connective tissue and bone marrow stromal cells into osteoblasts [4].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that nacre contains one or more signal molecules capable of activating osteogenic bone cells, in vivo and in vitro, leading to bone formation [19,20]. Water-soluble molecules diffusing from nacre powder are recognized by mammalian cells and induce recruitment and differentiation of fibroblasts from the connective tissue and bone marrow stromal cells into osteoblasts [4].…”
Section: Discussionmentioning
confidence: 99%
“…Testing of nacre has been carried out on human, rabbit, and sheep models [34,35]. In human patients, fresh woven bone bonded itself all the way through the nacre implant, augmented by the heightened activities of osteoblasts and osteoclasts.…”
Section: Marine Shellsmentioning
confidence: 99%
“…In human patients, fresh woven bone bonded itself all the way through the nacre implant, augmented by the heightened activities of osteoblasts and osteoclasts. Its degradation and resorption are limited even though nacre is stably tolerated in vivo, and this could impede its use within calcified tissue requiring rapid self-renewal [34,35]. While in some way controversial in definition, according to nacre researchers the "water-soluble matrix fraction" (WSM) of nacre directly induces bone formation [36].…”
Section: Marine Shellsmentioning
confidence: 99%
“…Although there are many thousands of types of nacre seashell from different marine molluscs, pearl oyster ( Pinctada maxima ) nacre is the only species so far tested and validated for osteoinduction. Pearl oyster nacre is able to induce osteogenesis and bone formation from latent osteoprogenitors along an endochondral pathway, consisting of a cartilage tissue intermediary phase (Lamghari et al, 2001a; 2001b; Lopez et al, 1992; 2004a; 2004b; Milet et al, 2004; Shen et al, 2006; Silve et al, 1992). Nacre has been tested in human, sheep and rabbit models (Lamghari et al, 1999; 2001b; Liao et al, 2002).…”
Section: Introductionmentioning
confidence: 99%